Organization and Dynamics of the Red Blood Cell Band 3 Anion Exchanger SLC4A1: Insights From Molecular Dynamics Simulations - Kalli, Antreas C.; Reithmeier, Reinhart A. F. (Frontiers in Physiology, 2022)
Molecular dynamic (MD) simulations have provided new insights into the organization and dynamics of the red blood cell Band 3 anion exchanger (AE1, SLC4A1). Band 3, like many solute carriers, works by an alternating access mode of transport where the protein rapidly (104/sec) changes its conformation between outward and inward-facing states via a transient occluded anion-bound intermediate. While structural studies of membrane proteins usually reveal valuable structural information, these studies provide a static view often in the presence of detergents. Membrane transporters are embedded in a lipid bilayer and associated lipids play a role in their folding and function. MD simulations of Band 3 in realistic lipid bilayers have revealed specific lipid and protein interactions and were used to re-create a model of the Wright (Wr) blood group antigen complex of Band 3 and Glycophorin A. Current MD studies of Band 3 and related transporters are focused on describing the trajectory of substrate binding and translocation in real time. A structure of the intact Band 3 protein has yet to be achieved experimentally, but cryo-electron microscopy in combination with MD simulations holds some promise to capture the conformational changes associated with anion transport in exquisite molecular detail.